El maracuyá en Florida - Mark Bailey; Ali Sarkhosh; Amir Rezazadeh; Joshua Anderson; Alan Chambers; Jonathan Crane; Jonathan Clavijo-Herrera (EDIS)
Passionfruit is a short-lived evergreen perennial vine that produces an aromatic, tropical-tasting fruit. This new 14-page Spanish translation of the UF/IFAS Horticultural Sciences Department provides a description of passionfruit and its various species and cultivars, as well as a guide to culture and management, harvest and storage, its pests and diseases, and food and marketing. By M. Bailey, A. Sarkhosh, A. Rezazadeh, J. Anderson, A. Chambers, and J. Crane. Translated by J. Clavijo-Herrer.